Multiple, Distinct Intercontinental Lineages but Isolation of Australian Populations in a Cosmopolitan Lichen-Forming Fungal Taxon, Psora decipiens (Psoraceae, Ascomycota) - Leavitt, Steven D.; Westberg, Martin; Nelsen, Matthew P.; Elix, John A.; Timdal, Einar; Sohrabi, Mohammad; St. Clair, Larry L.; Williams, Laura; Wedin, Mats; Lumbsch, H. T. (Frontiers in Microbiology, 2018)
Multiple drivers shape the spatial distribution of species, including dispersal capacity, niche incumbency, climate variability, orographic barriers, and plate tectonics. However, biogeographic patterns of fungi commonly do not fit conventional expectations based on studies of animals and plants. Fungi, in general, are known to occur across exceedingly broad, intercontinental distributions, including some important components of biological soil crust communities (BSCs), although molecular data often reveal unexpected biogeographic patterns in lichenized fungal species that are assumed to have cosmopolitan distributions. The lichen-forming fungal species Psora decipiens is found on all continents, except Antarctica and occurs in BSCs across diverse habitats, ranging from hot, arid deserts to alpine habitats. In order to better understand factors that shape population structure in cosmopolitan lichen-forming fungal species, we investigated biogeographic patterns in the cosmopolitan taxon P. decipiens, along with the closely related taxa P. crenata and P. saviczii. We generated a multi-locus sequence dataset based on a worldwide sampling of these taxa in order to reconstruct evolutionary relationships and explore phylogeographic patterns. Both P. crenata and P. decipiens were not recovered as monophyletic; and P. saviczii specimens were recovered as a monophyletic clade closely related to a number of lineages comprised of specimens representing P. decipiens. Striking phylogeographic patterns were observed for P. crenata, with populations from distinct geographic regions belonging to well-separated, monophyletic lineages. South African populations of P. crenata were further divided into well-supported sub-clades. While well-supported phylogenetic substructure was also observed for the nominal taxon P. decipiens, nearly all lineages were comprised of specimens collected from intercontinental populations. However, all Australian specimens representing P. decipiens were recovered within a single well-supported monophyletic clade consisting solely of Australian samples. Our study supports up to ten candidate species-level lineages in P. decipiens, based on genealogical concordance and coalescent-based species delimitation analyses. Our results support the general pattern of the biogeographic isolation of lichen-forming fungal populations in Australia, even in cases where closely related congeners have documented intercontinental distributions. Our study has important implications for understanding factors influencing diversification and distributions of lichens associated with BSC.